1997
DOI: 10.1038/385161a0
|View full text |Cite
|
Sign up to set email alerts
|

In vivo dendritic calcium dynamics in neocortical pyramidal neurons

Abstract: The dendrites of mammalian pyramidal neurons contain a rich collection of active conductances that can support Na+ and Ca2+ action potentials (for a review see ref. 1). The presence, site of initiation, and direction of propagation of Na+ and Ca2+ action potentials are, however, controversial, and seem to be sensitive to resting membrane potential, ionic composition, and degree of channel inactivation, and depend on the intensity and pattern of synaptic stimulation. This makes it difficult to extrapolate from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
529
2
3

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 758 publications
(547 citation statements)
references
References 30 publications
13
529
2
3
Order By: Relevance
“…During the time window of the SPW intracellular Ca 2+ may be increased by several cooperative mechanisms. Bursts of Na + -dependent action potentials may lead to Ca 2+ influx through voltage-gated Ca 2+ channels (Jaffe et al 1992;Svoboda et al 1997). Wide Ca 2+ spikes may further increase intracellular Ca 2+ levels (Jaffe et al 1992).…”
Section: Can Neuronal Connectivity Be Modified By Spw Bursts?mentioning
confidence: 99%
“…During the time window of the SPW intracellular Ca 2+ may be increased by several cooperative mechanisms. Bursts of Na + -dependent action potentials may lead to Ca 2+ influx through voltage-gated Ca 2+ channels (Jaffe et al 1992;Svoboda et al 1997). Wide Ca 2+ spikes may further increase intracellular Ca 2+ levels (Jaffe et al 1992).…”
Section: Can Neuronal Connectivity Be Modified By Spw Bursts?mentioning
confidence: 99%
“…For example, they are observed following presentation of visual stimuli (Hirsch et al 1995), whisker stimulation (Svoboda et al 1997), and during spontaneuous occurrence of hippocampal sharp wave (resulting from complex network-initiated spike bursts) in distal dendrites of pyramidal neurons in anesthetized animals in vivo (Komondi et al 1998). For a more detailed investigation of the electrophysiological characteristics of dendritic Ca 2ϩ potentials in pyramidal neurons, such potentials are often investigated in brain slices, following blockade of the Na ϩ and K ϩ channels (by external TTX ϩ TEA, or internal QX-314 ϩ Cs ϩ ) (Franz et al 1986;Sayer et al 1990Sayer et al , 1993Reuveni et Cd 2ϩ application to the proximal apical dendritic stem region (100-200 m from the soma) reduced the large subthreshold EPSP and abolished synaptically evoked action potentials, while having no effect on the EPSP evoked at Ϫ76mV.…”
Section: Apical Dendritic Compartment Of Deep Layer Pyramidal Corticamentioning
confidence: 99%
“…Sodium spike transients are generally required for triggering dendritic Ca 2ϩ channel activation (Chen et al 1997;Colbert and Johnston 1996; Komondi et al 1998;Markram et al 1995;Schiller et al 1995;Stuart and Sakmann 1994). In most cases, Na ϩ spikes are initiated in the axon and backpropagate into the apical dendrite (Stuart and Sakmann 1994;Stuart et al 1997;Colbert and Johnston 1996), where they have been shown to activate dendritic high-voltage-activated Ca 2ϩ channels both in vitro and in vivo (Buzsáki and Kandel 1998;Markram et al 1995;Schiller et al 1995;Spruston et al 1995;Stuart and Sakmann 1994;Svoboda et al 1997). Notably, when the timing of the arrival of the fast retrograde Na ϩ spikes temporally coincides with the afferent synaptic inputs, this Na ϩ spike-induced dendritic Ca 2ϩ influx is supralinear (i.e., greater than the linear sum of the effects of a backpropagated spike plus a synaptic input alone), and enduring changes in synaptic efficacy and strength of the previously weak afferent are induced (Markram et al 1997a;Magee and Johnston 1997).…”
mentioning
confidence: 99%
“…Cortical activity patterns have been studied previously in the mouse brain by optical imaging techniques, using voltage-and calcium-sensitive dyes and two-photon microscopy for increased penetration (Grinvald et al, 1986;Denk, 1995;Svoboda et al, 1997;Mrsic-Flogel et al, 2003). However, even with two-photon microscopy the depth of optical penetration is limited to several hundred microns, with the result that deep brain activity cannot be analyzed using optical imaging.…”
Section: Introductionmentioning
confidence: 99%